Are there first mover advantages for producers of energy-efficient appliances? The case of refrigerators. (October 2016) - Cleff, Thomas; Rennings, Klaus
Abstract: How can the position of countries competing for the energy efficiency market be assessed? To answer this question, we analyze the situation of the global refrigerator market. The lead market is Germany, followed by Korea und Italy. First mover advantages can be realised in Germany, backed by high European efficiency standards which diffuse after some years to other countries. Since the pay-off time for energy-efficient refrigerators is quite long, a second mover strategy with low prices is promising especially when electricity prices and national income are low, as in Asia and Russia. Some producers apply both strategies in different markets. Highlights: The paper presents an analysis of the potential lead markets for innovation in energy-efficient household appliances. Identification of six factors that drive a country's ability to become a lead market. Germany shows a strong lead market potential as the scores above average in all six factors, followed by Korea and Italy. Results of the indicator-based analysis are supported by interviews with experts from different countries.